Economic policy for the farm sector - Houthakker, Hendrik S.; American Enterprise Institute for Public Policy Research (Washington : American Enterprise Institute for Public Policy Research, 1967)
The main thrust of this study is that a rational farm policy does not involve any basic conflict between farmers and other groups. In the long run what is good for farmers, is good for the country, and conversely.
Includes bibliographical footnotes.
hza 05/07/2018
Loans
Keywords: Agriculture and state